2018
DOI: 10.1002/1878-0261.12322
|View full text |Cite
|
Sign up to set email alerts
|

GRP78‐mediated antioxidant response and ABC transporter activity confers chemoresistance to pancreatic cancer cells

Abstract: Chemoresistance is a major therapeutic challenge that plays a role in the poor statistical outcomes in pancreatic cancer. Unfolded protein response (UPR) is one of the homeostasis mechanisms in cancer cells that have been correlated with chemoresistance in a number of cancers including pancreatic cancer. In this study, we show that modulating glucose regulatory protein 78 (GRP78), the master regulator of the UPR, can have a profound effect on multiple pathways that mediate chemoresistance. Our study showed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…The top four biomarkers for NAC resistance, namely, GRP78, CADM1, PGES2, and RUXF demonstrated very high predictive ability for chemo-resistance with AUROC > 0.92. Notably, GRP78 has been previously demonstrated to play an important role in mediating chemoresistance in PDAC (15)(16)(17). Moreover, RUXF and PGES2 are known to be involved in chemo-resistance in ovarian and colorectal cancer, respectively (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The top four biomarkers for NAC resistance, namely, GRP78, CADM1, PGES2, and RUXF demonstrated very high predictive ability for chemo-resistance with AUROC > 0.92. Notably, GRP78 has been previously demonstrated to play an important role in mediating chemoresistance in PDAC (15)(16)(17). Moreover, RUXF and PGES2 are known to be involved in chemo-resistance in ovarian and colorectal cancer, respectively (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that high expression of GRP78 could promote tumorigenesis and drug resistance, and inhibition of GRP78 could improve the efficacy of chemotherapy drugs ( Huang et al, 2016 ; Dauer et al, 2018 ; Cook and Clarke, 2015 ). A clinical study, including 163 peripheral blood samples from non-small-cell lung cancer patients, revealed that GRP78 is highly enriched in advanced stages, significantly higher than seen in early-stage patients, which may be important in the carcinogenesis of non-small-cell lung cancer, and is associated with a poor prognosis ( Ma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 downregulation with siRNAs in combination with chemotherapeutics increased cell death compared to treatment or individual silencing. GRP78 downregulation also decreased ABC transporter activity, sensitising the PDAC cells to several chemotherapeutic agents [ 59 ]. GRP78 overexpression contributed to tumour angiogenesis independently of vascular endothelial growth factor (VEGF) and it increased AKT phosphorylation and ERK1/2 activation [ 60 ].…”
Section: Endoplasmic Reticulum Stress Response In Pdacmentioning
confidence: 99%